Efektifitas Hukum Jaminan dalam Hipotik Sektor Maritim: Studi Terhadap Kepastian Hukum dalam Perjanjian Kapal dan Property - Mamay Nilam Sari; Ainur Rohmah; Wasilul Arham; barok, lana; Ahmad Musadad (Universitas Medan Area, 2025)
This research discusses the implementation of ship mortgages within the Indonesian legal system, the legal certainty in ship mortgage agreements, regulatory challenges and alternative solutions, as well as the concept of security law in the maritime sector. A normative juridical method is employed in this study, utilizing statutory and comparative legal approaches. The findings indicate that the legal framework governing ship mortgages in Indonesia still contains several weaknesses, particularly in terms of legal certainty and the effectiveness of security enforcement. One of the primary issues is the absence of an integrated registration system, which creates difficulties in tracking the legal status of ships used as collateral. Additionally, the procedures for enforcing ship mortgages remain complex and time-consuming, often leading to uncertainty for creditors. A more comprehensive regulatory reform is needed to enhance the effectiveness of the maritime security law system. Harmonizing national regulations with international standards, strengthening the ship mortgage registration system, and improving the capacity of judicial institutions to handle maritime mortgage disputes are among the measures that can be taken. With such reforms, it is expected that a more effective legal system can be established-one that ensures the rights of creditors while also providing protection for debtors.